Characterisation of virus isolates associated with leaf yellowing in Swedish sugar-beet plants - Uddin, Mohammad Nasir (2010)
Plants of sugar beet with symptoms of virus infection (mosaic and yellowing) were collected from Skåne in Sweden for virus identification and characterization. To test the presence of Beet mosaic virus (BtMV) several detection methods were applied, such as: mechanical inoculation/transmission test with sugar beet (Beta vulgaris), red beet (Beta vulgaris) cv Rubia, spinach (Spinacia oleracea) cv Long Standing Bloomsdale and lettuce (Lactuca sativa) cv Sonette; DAS-Enzyme-linked Immunosorbent Assay (DAS-ELISA) with polyclonal antibody; RT-PCR amplification with Potyviridae-specific universal primers Sprimer/M4 (Chen et al., 2001), and BtMV-specific primer pairs BM1/BM2 and BM1/BM3 (Glasa et al., 2003). No BtMV infection was observed from the results of the tests mentioned above. To check the possible infection of beet polero/luteovirus, RT-PCR amplification was conducted with Luteoviridae-specific universal primers Lu1/Lu4 (Robertson et al., 1991) and the expected band of ca 500 bp was found for the collected samples. The PCR fragments of the isolates were cloned, sequenced and then used for phylogenetic analyses. The sequence information of the two Swedish isolates SE1 and SE2 collected from Skåne revealed a sequence of 505 nucleotides and they were found to be 100% identical to each other. Comparison to the sequences in GenBank using BLASTn search showed 99% nucleotide identity and 100% amino acid identity (using BLASTp & BLASTx) with the Coat Protein encoding region of Beet mild yellowing virus (BMYV) isolates. Phylogenetic analyses with different evolutionary best-fit models showed that both of the isolates are very closely related to the British isolate BMYV-Broom’s Barn. The sequence information of isolate SE1 was submitted to GenBank and the accession number FN827048 was obtained. To our knowledge, this is the first molecular identification and sequence information for BMYV from Sweden.